DISCRETE COSMOLOGY APPLICATION CONCERNING DARK MATTER HALOS - Brilenkov, R. D. (Одеські астрономічні публікації, 2016)
We applied discrete cosmology for investigation of the density profiles of dark matter (DM) halos of clusters of galaxies. Comparing the derived velocity dispersion with the experimental data for the Coma cluster, we found the effective radius for the mass distribution inside this galaxy cluster. Our estimates give an opportunity to restrict the parameters of the Navarro-Frenk-White profile for considered cluster.